StudyU: A Platform for Designing and Conducting Innovative Digital N-of-1 Trials - Stefan Konigorski; Sarah Wernicke; Tamara Slosarek; Alexander M Zenner; Nils Strelow; Darius F Ruether; Florian Henschel; Manisha Manaswini; Fabian Pottbäcker; Jonathan A Edelman; Babajide Owoyele; Matteo Danieletto; et al. (JMIR Publications, 2022)
N-of-1 trials are the gold standard study design to evaluate individual treatment effects and derive personalized treatment strategies. Digital tools have the potential to initiate a new era of N-of-1 trials in terms of scale and scope, but fully functional platforms are not yet available. Here, we present the open source StudyU platform, which includes the StudyU Designer and StudyU app. With the StudyU Designer, scientists are given a collaborative web application to digitally specify, publish, and conduct N-of-1 trials. The StudyU app is a smartphone app with innovative user-centric elements for participants to partake in trials published through the StudyU Designer to assess the effects of different interventions on their health. Thereby, the StudyU platform allows clinicians and researchers worldwide to easily design and conduct digital N-of-1 trials in a safe manner. We envision that StudyU can change the landscape of personalized treatments both for patients and healthy individuals, democratize and personalize evidence generation for self-optimization and medicine, and can be integrated in clinical practice.